Pre Soft Parameter Reduction From Soft Set - Mohammed, Mohammed Adam Taheir; Wan Maseri, Wan Mohd; Ruzaini, Abdullah Arshah (Asian Academic Research Associates, 2015)
The complexity induced by machine infinite stae cost the decisions resource such as CPU time. In solving this problem serarch space should be divided or decomposed into several sub sets in order to look for the informations which contains original characterstics. Identical of original set and it’s reductions induced two sets which measured by Jaccard similirtity to select the reductions were totally dominated against original characterstics. Searching process decomposed implises into several sub combinations eliminations as pre reductions which checked by decision partition cluster using Hybrid complement reduction. The decomposisions performances enhanced searching complexity and provided faster result in the process of decisions making generations